Morphology and phylogeny of two anaerobic freshwater ciliates: Brachonella comma sp. nov. and the widely distributed but little‐known caenomorphid, Ludio parvulus Penard, 1922. (20th February 2022) - Bourland, William; Pomahač, Ondřej; Čepička, Ivan
Abstract: Hypoxic, sulfidic freshwater sediments typically support a diffuse consortium of distinctive ciliated protists, including caenomorphids, metopids, and odontostomatids among others. A recent resurgence of interest in these important members of sapropelic food webs has resulted in the description of many new species and an effort, still in its infancy, to characterize them from a morphologic, molecular, and metabolic standpoint and to determine their phylogenetic relationships. Their seemingly invariable association with prokaryotic endosymbionts and, less commonly, ectosymbionts has become a focus for many researchers. In this report, based on morphologic and molecular data, we describe a Brachonella species (Ciliophora, Metopida) new to science and analyze its phylogeny. We also provide a morphologic and molecular characterization of the smallest representative of the Caenomorphidae Poche, 1913, Ludio parvulus Penard, 1922. The phylogenetic analysis confirms the inclusion of this species in the Caenomorphidae.